A Framework for Assessing Fiscal Vulnerability - Petrie, Murray (IMF Working Papers; Working Paper ;, 2000)
Fiscal vulnerability describes a situation where a government is exposed to the possibility of failure to meet its aggregate fiscal policy objectives. The suggested framework for assessing vulnerability highlights four macro-fiscal aspects of vulnerability: incorrect specification of the initial fiscal position; sensitivity of short-term fiscal outcomes to risk; threats to longer-term fiscal sustainability; and structural or institutional weaknesses affecting the design and implementation of fiscal policy. Fiscal vulnerability indicators are suggested.